LEADERSHIP, ORGANIZATIONAL COMMITMENT, WORK DISCIPLINE, AND EMPLOYEE PERFORMANCE AT PUBLIC HEALTH OFFICE OF PEKANBARU CITY - Mairia Mairia; Dadi Komardi; Harry Patuan Panjaitan (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study to determine and analyze the influence of leadership on organizational commitment and work discipline or employee performance in public health office of Pekanbaru City. This research was carried out at the public health office of Pekanbaru City with a sample of 99 people. The sampling technique in this study was saturated sampel by the census method. Data collection using a questionnaire. The data analysis technique used descriptive analysis and analysis hypothesis using the structural equation model (AMOS) and SPSS. The data analysis technique used descriptive analysis and hypothesis analysis using the structural equation model (AMOS) and SPSS. The test results show that there is an influence of leadership on organizational commitment, there is an influence of leadership on work discipline, there is no influence of leadership on employee performance, there is no influence of organizational commitment on work discipline, there is no influence of leadership on employee performance, and there is no influence of work discipline on employee performance.